Partizipation in Reallaboren in neuem Licht?! Ein Ansatz, die Lücke zwischen ko-kreativer und deliberativer Partizipation zu schließen - Sonnberger, Marco; Lindner, Doris (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
Sustainability-oriented real-world laboratories involve the co-design and co-creation of knowledge, based on a transdisciplinary cooperation between actors from different social worlds – academia, the administration, business, civil society – each endowed with specific interests, resources and worldviews. Sustainability-oriented real-world laboratories claim to be a means of inclusive participation in the co-creative shaping of solutions for socioecological issues and exploring pathways to sustainability. In the literature dealing with sustainability-oriented real-world laboratories, participation is thus mainly understood as active involvement by civil society, change agents and citizens in processes of experimentation and the implementation of solutions. We call this co-creative participation. However, participation in talk-based opinion formation and decision-making processes – we call this deliberative participation – is hardly discussed in the respective literature. In this paper, we argue that co-creative and deliberative participation are two forms of participation which can be conceptualized differently but which are both relevant for successful experimentation in sustainability-oriented real-world laboratories and are mainly intertwined in practice. We propose an ideal-typical conceptual framework for participation in sustainability-oriented real-world laboratories that combines co-creative and deliberative participation. The aim is to contribute to a systematization of, and rationale for, different forms of participation in real-world laboratories.
Keywords: Real-world laboratory; Co-creation; Participation; Deliberation; Real-world experiments; Sustainability